EDUCATIONAL CERTIFICATE VERIFICATION USING BLOCKCHAIN BASED FRAMEWORK. - S. K., GEETHA; G. R., SWEETHA PREETHI; R., SREENITHI (Turkish Journal of Physiotherapy Rehabilitation, 2021)
In this digitalized world, still there are some practices which are a bit tedious, one among those is the certificate verification process which is to be taken care. This complexity is overcome with the help of Blockchain technology which features its characteristics of transparency, immutability, and secure way of protecting data. In this work the certificates are digitalized and migrated to blocks using Ethereum Blockchain with SHA 256 working as the security algorithm. The documents in the database are encrypted and a unique hash code is generated with SHA 256. This hash code plays a vital role in the verification process which helps the requester in the final step. Added to that the certificate verified with the blockchain technology can be easily carried out with full security without the involvement of any intermediaries.